Vaccination against swine influenza in pigs causes different drift evolutionary patterns upon swine influenza virus experimental infection and reduces the likelihood of genomic reassortments - López-Valiñas, Álvaro; Valle, Marta; Wang, Miaomiao; Darji, Ayub; Cantero, Guillermo; Chiapponi, Chiara; Segalés, Joaquim; Ganges, Llilianne; Núñez, José I. (Frontiers in Cellular and Infection Microbiology, 2023)
Influenza A viruses (IAVs) can infect a wide variety of bird and mammal species. Their genome is characterized by 8 RNA single stranded segments. The low proofreading activity of their polymerases and the genomic reassortment between different IAVs subtypes allow them to continuously evolve, constituting a constant threat to human and animal health. In 2009, a pandemic of an IAV highlighted the importance of the swine host in IAVs adaptation between humans and birds. The swine population and the incidence of swine IAV is constantly growing. In previous studies, despite vaccination, swine IAV growth and evolution were proven in vaccinated and challenged animals. However, how vaccination can drive the evolutionary dynamics of swine IAV after coinfection with two subtypes is poorly studied. In the present study, vaccinated and nonvaccinated pigs were challenged by direct contact with H1N1 and H3N2 independent swine IAVs seeder pigs. Nasal swab samples were daily recovered and broncho-alveolar lavage fluid (BALF) was also collected at necropsy day from each pig for swine IAV detection and whole genome sequencing. In total, 39 swine IAV whole genome sequences were obtained by next generation sequencing from samples collected from both experimental groups. Subsequently, genomic, and evolutionary analyses were carried out to detect both, genomic reassortments and single nucleotide variants (SNV). Regarding the segments found per sample, the simultaneous presence of segments from both subtypes was much lower in vaccinated animals, indicating that the vaccine reduced the likelihood of genomic reassortment events. In relation to swine IAV intra-host diversity, a total of 239 and 74 SNV were detected within H1N1 and H3N2 subtypes, respectively. Different proportions of synonymous and nonsynonymous substitutions were found, indicating that vaccine may be influencing the main mechanism that shape swine IAV evolution, detecting natural, neutral, and purifying selection in the different analyzed scenarios. SNV were detected along the whole swine IAV genome with important nonsynonymous substitutions on polymerases, surface glycoproteins and nonstructural proteins, which may have an impact on virus replication, immune system escaping and virulence of virus, respectively. The present study further emphasized the vast evolutionary capacity of swine IAV, under natural infection and vaccination pressure scenarios.